The consequences of migration for the migrants' parents in Bolivia. (2nd January 2020) - BASTIA, TANJA; VALENZUELA, CLAUDIA CALSINA; POZO, MARIA ESTHER
Abstract: The existing literature on transnational care suggests that it is possible to care for ageing parents from afar. However, most of these studies are based on research in higher‐income countries, where families have access to institutional support and where travel and communication networks are generally of high quality. Studies focusing on lower‐income countries of origin have found a greater likelihood of migrants' parents being in a vulnerable situation. Here, though, there has been a preference for focusing on rural areas. In this article, we address this gap by reporting on a research project that spans rural, urban and peri‐urban areas, as well as different migration streams (regional South–South and South–North), and ask how migrants' parents fare during their adult children's absences in a context of very weak institutional support, widespread poverty and inequality. We find that parents in urban and peri‐urban areas are generally better able to negotiate their adult children's absences, while those in rural areas experience an increase in their vulnerability. However, there are also stories that are in tension with these general trends, which indicates that social networks, migrants' destinations and parents' socio‐economic statuses also mediate the availability of transnational care.